Gudangimpor.com, a new indonesian global supply chain and e-commerce solution - Wicaksono, Yuwono; S. Gunawan, Benny (The Indonesian Journal of Business Administration, 2016)
Abstract: In the current global conditions, the world leads in the globalization era. Globalization is the process of international integration arising from the interchange of worldviews, products, ideas and mutual sharing, and other aspects of culture. The fastest way to achieve goals as mentioned in the one of IMF journal about economic globalization is by joined in a regional, so it would make growing together in one regional in the same level of infrastructure. At the January 1st, 2016, Indonesia entered a new era of globalization. Indonesia joined with the other ASEAN countries to form AFTA (ASEAN Free Trade Area). Based on the definition of the finance department of the Republic of Indonesia, the ASEAN Free Trade Area (AFTA) is an agreement from the ASEAN countries to establish a free trade zone in order to improve the economic competitiveness of the region ASEAN with the make ASEAN as a production base of the world and as well as creating a regional market for 500 million population. Currently, Indonesia is entering the era of e-commerce boom. Where the emerging e-commerce that create new behavior in the Indonesian community of shopping. Moreover, it is still considered as a period of "education market" for most e-commerce so as to make the promo given very massive. Conditions above can be an opportunity for the purchasing service industry. To make purchases of products from e-commerce market or abroad, consumers encountered many obstacles ranging from communications to shipping constraints. To take advantage of the momentum, PT. GudangImpor Global Solution initiate to create a project related in this opportunities. This project is the extended of business of PT. GudangImpor Global Solution is a provider of product purchase, inspection, and comparison of prices overseas. Project aims to be a solution for retail customers in the purchase of products abroad are safe and simple by using e-commerce platform that is currently growing rapidly.Â Keywords: Globalization, purchasing service, e-commerce, GudangImpor